A new species of Megasoma Kirby (Coleoptera: Scarabaeidae: Dynastinae) from Sinaloa, Mexico - Morón, Miguel-Angel (Zootaxa, 2005)
A new species, Megasoma nogueirai sp. nov., from tropical subdeciduous forests at 290–820 m of altitude in Sinaloa, northwestern Mexico, is described and illustrated. Differences with M. elephas (F.) and M. occidentalis Bolívar, Jiménez and Martínez, are outlined.